TNF-TNFR1 Signaling Enhances the Protection Against Neospora caninum Infection - Ferreira França, Flávia Batista; Silva, Murilo Vieira; Silva, Mariana Ferreira; Ramos, Eliézer Lucas Pires; Miranda, Vanessa dos Santos; Mota, Caroline Martins; Santiago, Fernanda Maria; Mineo, José Roberto; Mineo, Tiago Wilson Patriarca (Frontiers in Cellular and Infection Microbiology, 2022)
Neospora caninum is a protozoan associated with abortions in ruminants and neuromuscular disease in dogs. Classically, the immune response against apicomplexan parasites is characterized by the production of proinflammatory cytokines, such as IL-12, IFN-γ and TNF. TNF is mainly produced during the acute phases of the infections and binds to TNF receptor 1 (CD120a, p55, TNFR1) activating a variety of cells, hence playing an important role in the induction of the inflammatory process against diverse pathogens. Thus, in this study, we aimed to evaluate the role of TNF in cellular and humoral immune responses during N. caninum infection. For this purpose, we used a mouse model of infection based on wildtype (WT) and genetically deficient C57BL/6 mice in TNFR1 (Tnfr1-/-). We observed that Tnfr1-/- mice presented higher mortality associated with inflammatory lesions and increased parasite burden in the brain after the infection with N. caninum tachyzoites. Moreover, Tnfr1-/- mice showed a reduction in nitric oxide (NO) levels in vivo. We also observed that Tnfr1-/- mice showed enhanced serum concentration of antigen-specific IgG2 subclass, while IgG1 production was significantly reduced compared to WT mice, suggesting that TNFR1 is required for regular IgG subclass production and antigen recognition. Based on our results, we conclude that the TNF-TNFR1 complex is crucial for mediating host resistance during the infection by N. caninum.